ردود ﻋﻠﻰ أوهﺎم ﺣﻮل ﺣﻖ ﺣﺮﻳﺔ اﻟﻤﺮأة ﻓﻲ اﻹﺳﻼم - Zawawi, Zawawi (IAIN Pekalongan, 2013)
Abstract : In the western, is still evolving paradigm that discredit Islam to curb the freedom of women and demeaning position. Consequently, there is a movement for